2021
DOI: 10.1083/jcb.202107070
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of human atlastin fusion activity reveals autoinhibition by the C terminus

Abstract: ER network formation depends on membrane fusion by the atlastin (ATL) GTPase. In humans, three paralogs are differentially expressed with divergent N- and C-terminal extensions, but their respective roles remain unknown. This is partly because, unlike Drosophila ATL, the fusion activity of human ATLs has not been reconstituted. Here, we report successful reconstitution of fusion activity by the human ATLs. Unexpectedly, the major splice isoforms of ATL1 and ATL2 are each autoinhibited, albeit to differing degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…To assay membrane fusion, we utilized D ATL protein purified from a HEK293-derived mammalian suspension cell line since our recent work revealed D ATL from these cells to be more active than protein purified from Escherichia coli ( Crosby et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…To assay membrane fusion, we utilized D ATL protein purified from a HEK293-derived mammalian suspension cell line since our recent work revealed D ATL from these cells to be more active than protein purified from Escherichia coli ( Crosby et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…For Drp1, target receptors and lipids likely fulfill these roles. Recent studies show that the extreme C-termini of the distantly related atlastins 49,50 , involved in ER membrane fusion, function in a similar autoregulatory capacity 50,51 . Thus, from an evolutionary standpoint, the extreme C-terminus may represent a critical, conserved, regulatory feature of all dynamin superfamily proteins (DSPs) 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial advances using D ATL, reconstitution of fusion activity by the human ATLs had proved refractory until recently, when our lab demonstrated that ATL1/2 expressed and purified from HEK cells, rather than E. coli , has robust fusion activity ( Crosby et al, 2022 ). Unexpectedly, fusion reconstitution also revealed that each contains a C-terminal autoinhibitory domain located just downstream of the required AH ( Crosby et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantial advances using D ATL, reconstitution of fusion activity by the human ATLs had proved refractory until recently, when our lab demonstrated that ATL1/2 expressed and purified from HEK cells, rather than E. coli , has robust fusion activity ( Crosby et al, 2022 ). Unexpectedly, fusion reconstitution also revealed that each contains a C-terminal autoinhibitory domain located just downstream of the required AH ( Crosby et al, 2022 ). For ATL2, the presence of the C-terminal extension inhibits fusion to the extent that the full-length purified protein lacks nearly all detectable activity, and removal of the extension increases the initial fusion rate by 500-fold.…”
Section: Introductionmentioning
confidence: 99%